Presentation, Characteristics and Features of Lymphoma in a Retrospective Case Series of Patients with Sjogren’s Disease - Jennifer Behbodikhah; Lisa Balistreri; Steven E. Carsons (Rheumato)
Sjogren’s Disease (SjD) is associated with an increased risk of lymphoma. We investigated the prevalence of lymphoma in a retrospective case series of patients with SjD and reported on the clinical presentation, treatment, response, and outcome. A retrospective review of 132 patients diagnosed with Sjogren’s Disease was conducted at our institution from June 2000 to November 2023, and 10 cases of malignant lymphoma were identified. Clinical and biological markers known to be predictors of lymphoma, as well as lymphoma characteristics, were examined. The most common predictive lab findings were hypergammaglobulinemia, the rheumatoid factor, and lymphopenia. Persistent parotid gland enlargement was also found in greater than 50% of patients. The majority of patients were Caucasian females, and the average time between the diagnosis of SjD and lymphoma was 14.3 years. The median age at lymphoma diagnosis was 59.5 years, with 9 out of 10 lymphomas identified as non-Hodgkin lymphoma, the majority of cases being mucosa-associated lymphoid tissue (MALT) lymphoma. We identified similarities in our series, such as laboratory markers and clinical symptoms, to those previously identified as possible predictors of lymphoma development. These factors may be useful in determining the risk of malignancy development and justify the need for long-term monitoring, as well as provider education and awareness.